KREDIBILITAS GUS DUR SEBAGAI KOMUNIKATOR POLITIK DALAM PROSES DEMOKRATISASI DI INDONESIA - nurkholisoh, nurkholisoh (Universitas Prof. Dr. Moestopo (Beragama), 2010)
Nahdathul Ulama (NU), Gus Dur and Democratization in Indonesia summarized in this paper. How is the credÂ ibility of Gus Dur as a statesman of political communication to bring the values of democracy. Â This qualitative research study will explore more deeply about who Gus Dur is packed with biographical research method, this research makes a reference that should be a reference.